Fatherhood in Egypt: Identity Formation and Role Theory Perspectives - Gawdat, Mahmoud Nasr (AUC Knowledge Fountain, 2026)
Fatherhood is a central yet under-researched dimension of family life in Egypt, particularly from a psychological and identity-based perspective. This study explores how Egyptian fathers construct and experience fatherhood through the lenses of identity theory and role theory. Using a qualitative research design, seven focus groups were conducted with 43 Egyptian fathers to examine the meanings they attribute to fatherhood, their perceived roles, challenges, support systems, and personal transformations. Thematic analysis revealed six interconnected themes: (1) describing the father’s role, (2) learning the father role, (3) social and cultural influences on the father role, (4) meaning of being a father, (5) challenges and difficulties with the father role, and (6) support systems for the father role. Findings indicated that fatherhood constitutes a core identity for participants, shaped by emotional bonds, moral responsibility, religious values, and intergenerational experiences. Fathers experienced significant role strain arising from economic pressures, work–family conflict, limited institutional support, and cultural expectations surrounding masculinity and emotional expression. Despite these challenges, participants demonstrated strong reflective capacity and aspiration toward more emotionally engaged and nurturing forms of fatherhood. The study underscores the dynamic interaction between identity and role processes in shaping Egyptian fatherhood and highlights a critical gap in father-focused psychosocial and policy support. Implications for family policy, mental health services, and culturally grounded fatherhood interventions in Egypt are discussed.